The Influence of Thinking Aloud Pair Problem Solving (TAPPS) Learning Model Charged Science Literacy on Students Learning Competencies in the Material of Human Reproductive System at SMAN 1 Enam Lingkung - Intan Maghvira; Relsas Yogica; Ganda Hijrah Selaras; Syamsurizal Syamsurizal (Universitas Negeri Padang, 2019)
The Problem of the research at SMAN 1 Enam Lingkung was that the Biology learning process is less varied and teacher-centered, students were unable to solve problems in learning, low learning competencies of students from aspects of knowledge, attitudes, and skills,and low science literacy abilities of students. The purpose of this study was to determine the effect of applying thinking aloud pair problem solving learning model with science literacy on students learning competencies in human reproductive system material at SMAN 1 Enam Lingkung.This type of research is an experiment with a randomized control group post-only only design. The population was all class XI of SMAN 1 Enam Lingkung which were registered in the 2018/2019.Sampling was done using cluster random sampling, and the chosen sample was the XI MIPA 2 class as the experimental class, and the XI MIPA 1 class as the control class. The instruments used were in the form of posttest questions for knowledge competency, observation sheets for attitude and skill competencies. Based on the results of the knowledge competency research, the tcount was 5.14> ttable 1.67, the competency attitude was tcount of 15.12> ttable 1.67, and in the competency of skills tcount was 9.45> t table 1.67. This is an aceppted hypothesis. It was concluded that the model thinking aloud pair problems solving with sains literacy improve the competencies of knewledge, attitude, and skills in the material of the human reproductive system at SMAN 1 Enam Lingkung.